Kualitas Pelayanan Publik Bidang Administrasikependudukan (Studi Pelayanan Publik Bidang Administrasi Kependudukan Di Kelurahan Cempaka Putih Barat) - Camelia Rahmayanti; Tri Ubayanto (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
The purpose of this study is to find out how the quality of public services in the field of population administration in Cempaka Putih Barat Village is. This research method uses descriptive qualitative method. Data collection techniques using observation techniques, in-depth interviews, literature studies both printed and online. The results of this study prove that in terms of physical evidence (tangible) Kelurahan Cempaka Putih Barat has an area of 8x6m2 for a total of 5 service staff. The service room has a service desk, work desk, identification card recording device, 2 sets of back and a long chair that is intended for people waiting for service. In the aspect of reliability (reliability), the results of the study revealed that the people of Cempaka Putih Barat Village were satisfied with the services provided by the responsiveness aspect of employees in terms of helping people who need services, especially people who are confused by the services that have been seen between officers and visitors who communicate with each other. . Assurance aspects, especially security at the Cempaka Putih Barat Village Office, Central Jakarta, have shown efforts to improve the quality of their services related to providing a sense of security for the community. The aspect of empathy (empathy), which is given by the Cempaka Putih Barat Village is by giving a pleasant impression. The aspect of empathy (empathy), which is given by the Cempaka Putih Barat Village is by giving a pleasant impression.